2021
DOI: 10.1063/5.0037333
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-based ionic liquids as rheological modifiers of heavy crude oil: An experimental and theoretical study

Abstract: Two series of imidazolium-based ionic liquids (ILs) were tested as rheological modifiers of heavy crude oils. ILs with the 1-butyl-3-alkylimidazolium cation optimize the effect on viscosity at low concentrations, whereas those with the 1-benzyl-3-alkylimidazolium cation are similarly effective only at higher concentrations, which is due to a stronger IL–IL interaction with respect to the IL–asphaltene interaction. The most effective ILs were [C6bim][PF6], [phetbim][PF6], and [C9bim][NTf2], with viscosity falli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Zhu et al 22 chose a [C 16 mimCl]/ndodecane/n-pentanol/water microemulsion system to separate coal slime from coal, which signicantly decreased the treatment cost. Martínez-Mora et al 23 found that the length of the alkyl chain and charge density of anion ions inuenced the p-p interaction between asphaltenes, i.e., cations with longer alkyl chains could disperse asphaltenes better. Moreover, ILs containing Cl − were more effective in hindering p-p interactions than those containing Br − , BF 4 − , or PF 6…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 22 chose a [C 16 mimCl]/ndodecane/n-pentanol/water microemulsion system to separate coal slime from coal, which signicantly decreased the treatment cost. Martínez-Mora et al 23 found that the length of the alkyl chain and charge density of anion ions inuenced the p-p interaction between asphaltenes, i.e., cations with longer alkyl chains could disperse asphaltenes better. Moreover, ILs containing Cl − were more effective in hindering p-p interactions than those containing Br − , BF 4 − , or PF 6…”
Section: Introductionmentioning
confidence: 99%
“…C 23 H 36 BrN IL was more effective in reducing the viscosity of the heavy crude oil in comparison to the C 18 H 35 BrN 2 , C 19 H 34 BrN, C 23 H 42 Br 2 N 4 , C 23 H 39 BrN 2 , and C 17 H 38 BrN ILs. Martinez-Mora et al performed experimental and theoretical analysis of heavy crude oil rheological properties in the presence of imidazolium-based ILs. Their results showed that the considered 24 ILs reduced the viscosity of the heavy crude oil, where ILs [C 6 bim]­[PF 6 ], [phetbim]­[PF 6 ], and [C 9 bim]­[NTf 2 ] were the most effective in reducing the viscosity in comparison to other considered ILs.…”
Section: Introductionmentioning
confidence: 99%